TECHNOLOGY AND THE EMPOWERMENT OF RURAL WOMEN AND GIRLS IN 4TH INDUSTRIAL REVOLUTION - Rozak, Norizan Abdul; Anua Jah, Nurain Jantan (PALASTREN: Jurnal Studi Gender, 2019)
ABSTRACTThe purpose of the paper is to present the initiatives of providing access of internet to rural women and girls while highlighting the status quo of the digital literacy between Malaysian women and men, and the impacts of the initiatives done on digital literacy from 2015 until now. The research relies heavily on information from official documents, research publications, reports from relevant agencies, and secondary data from existing government statistics. From the information and data culled, several initiatives in providing access of internet to rural women and girls are taken by the government but the percentage of digital literacy between Malaysian women and men remains constant. Malaysian women have made significant progress and the search for greater gender equality has been relatively successful. Rural women and girls developments are essential as it will help in shaping the future of our country towards positive directions.